Splitting Orders in Fragmented Markets - Bert Menkveld (Tinbergen Institute, 2001)
A number of recent theoretical studies have explored trading in fragmented markets, e.g. Biais etal. (2000), a phenomenon increasingly witnessed in modern markets. The key assumptiongenerating the results is that there is at least one liquidity demander exploiting access to allmarkets by optimally splitting orders across markets. This paper seeks to test this assumnption ina natural experiment involving Dutch stocks that are traded both in Amsterdam and New York. Theresults confirm the presence of rational, order splitting traders. This explains the increased volumeand relatively large and persistent price changes for the overlapping period.
Keywords: G1; G12; G14; G15; 330; Wertpapierhandel; Börse; Börsenmakler; Anlageverhalten; Marktmikrostruktur; Theorie